An Iconic Representation of Modern Architecture from Construction to Destruction: Tercuman Newspaper Building - Zeynep Yanılmaz (Iconarp International Journal of Architecture and Planning, 2025)
The study focuses on the Tercüman Newspaper Building, which has recently drawn attention following its demolition. The Tercüman Newspaper Building was built in 1974 based on a project selected through a competition organized by Kemal Ilıcak. The architects of the building, Günay Çilingiroğlu and Muhlis Tunca, were influential figures in shaping the modern architectural practices of the period. In addition to the architects' design approach and education, Kemal Ilıcak's vision played a key role in shaping the building's architecture. The Tercüman Newspaper Building, one of the first examples of New Brutalism in Türkiye in the 1970s, stood out as a modern heritage structure that gained attention for its innovative structural analysis. Over its 49-year existence, the building was widely discussed both for its architectural design and its symbolic value. This study aims to examine the building's functional transformations from its construction to its demolition and contribute to its role in social memory. The first stage of the study, structured in four phases, establishes the theoretical framework and discusses demolition and conservation actions in the context of modern architecture. The second stage provides details on the plan, structure, and façade characteristics of the building, along with an analysis of its symbolic value. The third stage examines the functional changes the newspaper building underwent after changing ownership and the process leading to its demolition, also exploring the public reactions to the demolition. The fourth and final stage emphasizes that modern heritage buildings, which reflect the architectural practices and socio-cultural life of a period and should be preserved for future generations through a robust conservation mindset.